Implementation of Quality Management Based on the POAC Approach in Improving Teacher Quality - Shalih, Badrus; Dainuri, Muhamad Rifan; Iman, Azis Nurul; Nurul Azira (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2026)
Improving the quality of teachers is a key factor in realizing the quality of sustainable madrasah education, but there are still many madrasas facing limited resources and have not implemented quality management systematically. This study aims to analyze the implementation of quality management based on the POAC (Planning, Organizing, Actuating, and Controlling) approach in improving the quality of teachers at MI Miftahul Ulum Panyiuran and examine its integration with the values of Islamic education management. The research uses a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observations, and documentation studies, then analyzed using Miles and Huberman's interactive model. The results of the study showed that planning was carried out in a participatory manner through RKM and RPT, competency-based organization and deliberation, implementation through continuous training and comparative studies, and evaluation through supervision and program evaluation. The implementation of POAC has an impact on improving teacher professionalism, a culture of cooperation, a conducive learning climate, and a quality culture. The integration of the values of tadbir, syūrā, tarbiyah, and muḥāsabah strengthens the moral-spiritual dimension, although there is still a need for more measurable quality indicators.